GNX-4728, a novel small molecule drug inhibitor of mitochondrial permeability transition, is therapeutic in a mouse model of amyotrophic lateral sclerosis - Martin, Lee J.; Fancelli, Daniele; Wong, Margaret; Niedzwiecki, Mark; Ballarini, Marco; Plyte, Simon; Chang, Qing (Frontiers in Cellular Neuroscience, 2014)
Amyotrophic lateral sclerosis (ALS) is a fatal neurological disorder in humans characterized by progressive degeneration of skeletal muscle and motor neurons in spinal cord, brainstem, and cerebral cortex causing skeletal muscle paralysis, respiratory insufficiency, and death. There are no cures or effective treatments for ALS. ALS can be inherited, but most cases are not associated with a family history of the disease. Mitochondria have been implicated in the pathogenesis but definitive proof of causal mechanisms is lacking. Identification of new clinically translatable disease mechanism-based molecular targets and small molecule drug candidates are needed for ALS patients. We tested the hypothesis in an animal model that drug modulation of the mitochondrial permeability transition pore (mPTP) is therapeutic in ALS. A prospective randomized placebo-controlled drug trial was done in a transgenic mouse model of ALS. We explored GNX-4728 as a therapeutic drug. GNX-4728 inhibits mPTP opening as evidenced by increased mitochondrial calcium retention capacity both in vitro and in vivo. Chronic systemic treatment of G37R-human mutant superoxide dismutase-1 (hSOD1) transgenic mice with GNX-4728 resulted in major therapeutic benefits. GNX-4728 slowed disease progression and significantly improved motor function. The survival of ALS mice was increased significantly by GNX-4728 treatment as evidence by a nearly 2-fold extension of lifespan (360 days to 750 days). GNX-4728 protected against motor neuron degeneration and mitochondrial degeneration, attenuated spinal cord inflammation, and preserved neuromuscular junction innervation in the diaphragm in ALS mice. This work demonstrates that a mPTP-acting drug has major disease-modifying efficacy in a preclinical mouse model of ALS and establishes mitochondrial calcium retention, and indirectly the mPTP, as targets for ALS drug development.